Peran Budaya Organisasi Dalam Memoderasi Good Governance Dan Sistem Pengendalian Internal Terhadap Kinerja Pegawai - Risakotta, Kathleen Asyera (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2025)
This research aims to explore whether good governance and internal control systems influence employee performance with organizational culture as a moderating variable. The population studied was all BPKAD employees of Maluku Province and the sample selection technique used the saturated sample method with a total of 53 employees. The data analyzed in this research is primary data obtained through distributing questionnaires. The findings from this research show that there is an influence between good governance and the internal control system on employee performance, organizational culture strengthens the relationship between good governance and employee performance, and organizational culture also strengthens the relationship between the internal control system and employee performance.